An integrated study on brand choise and brand loyalty in Turkish white goods market - Haskan, Murat (My University, 1995)
unknown
Keywords: Genel yönetim; GIDA SANAYİ-PAZAR DURUMU; GIDA SANAYİ-TÜRKİYE; Pazar araştırması ve analizi; Pazarlama yönetimi